Effect of afterload reduction in patients with ventricular and physiological pacing. Issue 3 (March 1984) - Been, M; de Bono, D P; Miller, H C; Hillis, W S
Abstract : The effect of afterload reduction was studied in a group of patients who remained breathless or tired after permanent ventricular pacing. Haemodynamic measurements were made before and after giving hydralazine 20 mg intravenously using a triple lumen thermodilution catheter and cuff blood pressure recordings during ventricular pacing at the standard rate of 71/min or an increased rate of 88/min and physiological pacing. Increasing the ventricular pacing rate had no effect on cardiac output as stroke volume fell. Hydralazine produced a greater rise in cardiac output than physiological pacing alone, although peak values were obtained by combining the two. Ventricular pacing produced intermittent large left and right atrial pressure peaks. Physiological pacing produced no such peaks, and mean right and left atrial pressures fell. Hydralazine did not significantly alter atrial pressures. These findings show that in these patients, most of whom had a low cardiac output, afterload reduction with ventricular pacing increased resting cardiac output more than physiological pacing alone. Nevertheless, persistence of high filling pressures despite afterload reduction may limit the potential therapeutic benefit. Care should be taken in extrapolating these data to other patient groups.